Post Stroke Care Education on Knowledge and Skills in Carrying out ROM Using Audio Visual Media - Rondonuwu, Rolly H. S.; Pesak, Ellen; Massie, Timothy Ch; Sarimin, Dorce Sisfiani (International Journal of Science and Society, 2024)
Stroke is the second leading cause of death and the third leading cause of disability. One in four people is at risk of stroke, there are more than 12.2 million new strokes every year. stroke in Indonesia was 10.9%, and in North Sulawesi province it was 14.2%, and the intervention used in this study was Range of motion (ROM). This research aims to determine the influence of post-stroke care education on the knowledge and range of motion skills of the Silian village community using audio-visual media. This research method is quantitative, with a pre-experimental one-group pre-test and post-test design. The 30 sample respondents used the Random Sampling Technique. The treatment was carried out with Post Stroke Care Education using audio-visual media, exercises were carried out in 30 minutes for 3 days. Skill observation sheet instruments and questionnaires regarding Stroke and ROM using the Paired T-test. The research conducted had significant results where sesewanua was more effective than water with a P value of 0.002. The data results mean that the pretest knowledge is 6.90 and the post-test is 15.50, the average increase in knowledge is 7.93. The pretest skills score is 0.00 and the posttest is 23.43. Further tests using the Paired T-test showed that there was a significant effect of post-stroke care education on a range of motion knowledge (P value 0.00; α 0.05) and there was a significant effect of post-stroke care education on a range of motion skills (P value 0.00; α 0.05). The conclusion is that post-stroke care education increases respondents' knowledge and skills regarding range of motion.